Pattern and etiological factors of surgical site infection among patients undergone surgery at Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh - Islam, Mohammad Jayedul; Md, Rasell; Majumdar, Krisna Rani; Islam, K. M. Shaiful; Muhammad Iqbal, Abu Khaled (International Surgery Journal, 2021)
Background: Surgical site infections (SSIs) has been reported to be one of the most common causes of nosocomial infections which accounting for 20% to 25% worldwide. Despite recent advances in aseptic techniques, SSIs continue to be a major source of morbidity and mortality in developing countries and continue to represent about a fifth of all healthcare-associated infections. The aim of the study was to assess the pattern and etiological factors of surgical site infection among the patients who had undergone in surgery. Methods: This study was a cross-sectional study conducted at the department of surgery in Sir Salimullah Medical College and Mitford Hospital (SSMC and MH), Dhaka, Bangladesh from August 2017 to July 2018. Total 160 admitted patients who had undergone surgical procedures during the study period were assessed and interviewed. Results: The mean±SD age of the participants was 51.79±11.30 SD years. About 59% were male and 41% were female. Most of them came from rural areas (61%). Surgeries were done in different indications and 21% developed SSI. Of all SSIs, 73% were superficial and 27% were deep infections. The most common organism involved in SSI was S. aureas (42.4%), followed by E. coli (27.3%), P. aeruginosa (12.1%), bacteroids (12.1%), and Klebsiella spp. (6.1%). Meropenem was the most sensitive drug followed by Ceftriaxone. Gentamycin showed cent percent sensitivity on the gram-negative organisms. Conclusions: The incidence of SSIs was found in about one-fifth of the post-surgical cases, where Staphylococcus aureus was the most prevalent organism.